Isoconversional kinetic analysis of stoichiometric and off-stoichiometric epoxy-amine cures - Sbirrazzuoli, Nicolas; Mititelu-Mija, Alice; Vincent, Luc; Alzina, Camille (Thermochimica acta, 2006)
The curing reaction of stoichiometric and off-stoichiometric diglycidyl ether of bisphenol A (DGEBA) and 1,3-phenylene diamine ( m-PDA) mixtures was studied by differential scanning calorimetry, thermogravimetric analysis and rheological measurements. In order to highlight the side reactions such as etherification and homopolymerization, the neat DGEBA and DGEBA/DMBA ( N, N-dimethylbenzylamine) mixture were examined. The classical model-fitting and the advanced isoconversional methods were used to determine the activation energy of the different reactions. The advanced isoconversional method leads to a good agreement between isothermal, nonisothermal and rheological results. The effective activation energies of primary amine epoxy reaction, etherification and homopolymerization were estimated to about 55–60, 104 and 170 kJ mol −1, respectively.